Erythema nodosum leads to the diagnosis of pulmonary tuberculosis - Koufakis, Theocharis (Pan Afr Med J, 2014)
Erythema nodosum is a panniculitis which may have various causes, such as drugs, infections, sarcoidosis, inflammatory bowel disease, tuberculosis or can be idiopathic. We here report a case of a womandiagnosed with pulmonary tuberculosis whose first symptom was erythema nodosum. A thorough clinical and laboratory investigation of the patient presenting with erythema nodosum is always required, in order to assess a possible systemic, underlying condition.